Health promotion and disease prevention from the perspective of active aging (Research, Society and Development, 2020)
Objectives: to know the perception of the participants of a health promotion and disease prevention group on the contributions of the activities carried out to adhere to the treatment of Chronic Noncommunicable Diseases and to improve or maintain the health condition and identify whether the participants relate health promotion and disease prevention activities to the search for active aging. Methodology: descriptive exploratory study, with a qualitative approach, realized with 15 people who attended the Vida e Saúde, group of the Family Health Strategy Unit of a municipality in the south of Brazil, from February to March 2019. The collection of data was through semi-structured and recorded individual interviews. Thematic Analysis was used for data analysis. Results: presented in the following categories Encouraging the incorporation of healthy habits into the daily routine; Pain control; The group as a welcoming place; The group as a means of access to information and social interaction. The activities carried out in the Vida e Saúde group are perceived by the participants as positive and that encourage active aging, self-care and the adoption of healthy habits. Conclusion: it was possible to identify the importance of the group and the approach of Chronic Noncommunicable Diseases, health education actions and activities developed for these participants, even with the unusual use of the terms “chronic disease” and “integrative and complementary practices” by participants.